Over 130,000 farmers in the Mekong Delta, Vietnam, have used timely weather forecasts and advisories to improve farm decisions, leading to higher yields and profits - Swaans, Cornelis; Barlis, Angelica; Le, Tam Thi (2023)
Through "Local Technical Agroclimatic Committees" (LTACs) and multiple media, timely Agro-Climatic Bulletins are being disseminated to over 130,000 farmers (520,000 beneficiaries) in 351 communities in Vietnam’s Mekong Delta and South-Central Coast. Based on a sample survey of 202 farmers in one province, the use of this information has enabled farmers to increase their rice yields and revenue significantly. The LTAC model was developed in Latin America by CIAT and has been successfully adapted to the southeast Asian context.